Characterization of very late dysphagia after chemoradiation for oropharyngeal squamous cell carcinoma. (December 2020) - Gharzai, Laila A.; Li, Pin; Schipper, Matthew J.; Yao, John; Mayo, Charles S.; Wilkie, Joel R.; Hawkins, Peter G.; Lyden, Teresa; Blakely, Anna; Ibrahim, Mohannad; Schonewolf, Caitlin A.; Shah, Jennifer; et al.
Highlights: Late dysphagia in oropharyngeal cancer after treatment is poorly characterized. We report long-term dysphagia outcomes in patients treated with chemoradiation. 15.1% of patients had moderate dysphagia >2.5 years after treatment. 7.5% of these patients had dysphagia that worsened after one year out from treatment. Radiation dose to the tongue may be a target to prevent this and should be further studied. Abstract: Objectives: Improved prognosis for p16+ oropharyngeal squamous cell carcinoma (OPSCC) has led to efforts to mitigate long-term complications of treatment, which remains poorly defined in late survivors. Here we characterize very late dysphagia in OPSCC. Materials and methods: Long-term review of 93 p16+ OPSCC patients treated with chemoradiation was performed. We scored videofluoroscopic swallow studies (VFSS) according to the Dynamic Imaging Grade of Swallowing Toxicity (DIGEST) scale. Very late dysphagia was defined >2.5 years from end of treatment. Fine-Gray regression models were used to assess dysphagia with competing risk of death. Results: Median follow up was 10.5 years. 402 total VFSS were assessed (median 4 per patient, range 0–8). 15.1% of patients had a DIGEST score ≥2 very late after treatment. Very late DIGEST score ≥2 correlated with T-stage (HR 1.7, p = 0.049), second cancer (HR 6.5, p = 0.004), superior pharyngeal constrictor dose (HR 1.11, p = 0.050), total tongue dose (HR 1.07, p = 0.045), but not hypoglossal nerve dose (p > 0.2). Seven patients (7.5%) had late progressive dysphagia, defined as DIGEST score that increased by ≥2 beyond one year after treatment, and this correlated with higher ipsilateral hypoglossal nerve D1cc dose (75 vs 72 Gy, p = 0.037). Conclusion: In p16+ OPSCC patients treated with definitive chemoradiation, at least 7.5% developed late progressive dysphagia, and 15.1% experienced moderate dysphagia >2.5 years from treatment. Our study suggests that dose to tongue musculature may be associated with very late dysphagia, and hypoglossal nerve dose may be associated with late progressive dysphagia. More intensive long-term dysphagia survivorship monitoring is suggested.